Quality Disclosure and Certification: Theory and Practice - Dranove, David; Jin, Ginger Zhe (Journal of Economic Literature, 2010)
This essay reviews the theoretical and empirical literature on quality disclosure and certification. After comparing quality disclosure with other quality assurance mechanisms and describing a brief history of quality disclosure, we address two sets of theoretical issues. First, why don't sellers voluntarily disclose through a process of “unraveling” and, given the lack of unraveling, is it desirable to mandate seller disclosure? Second, when we rely on certifiers to act as the intermediary of quality disclosure, do certifiers necessarily report unbiased and accurate information? We further review empirical evidence on these issues, with a particular focus on healthcare, education, and finance. The empirical review covers quality measurement, the effect of third-party disclosure on consumer choice and seller behavior, as well as the economics of certifiers. (JEL D18, K32, L15, M31)